(Ⅰ)∵Sn=an+1-2n+1+1(n∈N*),且a1=1,
∴S1=a2-22+1,a1=a2-22+1,∴a2=4,
S2=a3-23+1,a1+a2=a3-23+1,∴a3=12;
(Ⅱ)由Sn=an+1-2n+1+1,(n∈N*)①,
得Sn-1=an-2n+1,(n∈N*,n≥2)②,
①-②得:an=an+1-an-2n,即an+1=2an+2n(n≥2),
检验知a1=1,a2=4满足an+1=2an+2n(n≥2).
∴an+1=2an+2n(n≥1).
变形可得=+1(n≥1).
∵==1,
∴数列{}是以1为首项,1为公差的等差数列.
∴=1+(n-1)×1=n,
则an=n•2n-1(n≥1);
(Ⅲ)证明:由(Ⅱ)知an=n•2n-1(n≥1),代入bn=
得bn==1-,
∵22n+1-(n+1)•2n-2=(2n+1-n-1-)2n>0,
∴(n+1)•2n+2<22n+1
又∵2n+1<(n+1)•2n+2,
∴2n+1<(n+1)•2n+2<22n+1,
则<<
∴1-<1-<1-
∴1-<bn<1-
∴n-(++…+)<Tn<n-(++…+)
即n-3×<Tn<n-3×
∴n-[1-()n]<Tn<n-[1-()n]
∴n-<Tn<n-<n-.